Ferritic stainless steel with improved corrosion resistance and magnetic properties and manufacturing method thereof
By optimizing alloy composition and manufacturing processes, the ferritic stainless steel achieves both high corrosion resistance and magnetic permeability, addressing the limitations of existing technologies and improving its performance in electronic devices.
Patent Information
- Application Number
- JP2024527352
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-17
- Filing Date
- 2022-10-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-10-25
AI Technical Summary
Existing ferritic stainless steels struggle to simultaneously achieve high corrosion resistance and magnetic permeability, limiting their application in electronic devices prone to electromagnetic interference.
Optimizing alloy composition with specific weight percentages of C, N, Si, Mn, Cr, Mo, Nb, Ti, and controlling manufacturing processes such as reheating, hot and cold rolling annealing, and pickling to achieve a ferritic stainless steel with improved corrosion resistance and magnetic properties.
The optimized ferritic stainless steel exhibits a pitting potential of 200 mV or more for corrosion resistance and a maximum magnetic permeability of 1,000 or more in the 50 Hz frequency band, enhancing its suitability for electronic devices.
Smart Images

Figure 2024546015000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel having improved corrosion resistance and magnetic properties and a manufacturing method thereof, and more particularly to a ferritic stainless steel having improved corrosion resistance and magnetic properties by optimizing alloy components and manufacturing processes, and a manufacturing method thereof. [Background technology]
[0002] Recently, with the development of technology fields such as smartphones and semi-autonomous cars, the use of various electronic devices has led to a rapid increase in the use of electromagnetic waves. This has led to an increase in electromagnetic interference between electronic devices. Electromagnetic interference can cause devices to malfunction or make precise control of devices difficult. To prevent electronic devices from malfunctioning due to electromagnetic interference, important parts must be surrounded by materials that can shield against magnetic fields. On the other hand, ferritic stainless steel has a relatively high magnetic permeability and is also corrosion resistant, making it a versatile material that can be used in a variety of applications where both corrosion resistance and shielding functions are required. However, there have not been many technologies that can simultaneously provide high corrosion resistance and high magnetic permeability.
[0003] In Patent Document 1, an attempt was made to provide a ferritic stainless steel with improved corrosion resistance by controlling the contents of Si, Ti, Nb, and Al. However, the high magnetic permeability required for use in electronic devices could not be ensured. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Korean Patent No. 10-2302386 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve the above problems, and its object is to provide a ferritic stainless steel having improved corrosion resistance and magnetic properties by optimizing the alloy components and manufacturing process, and a manufacturing method thereof. [Means for solving the problem]
[0006] The ferritic stainless steel of the present invention with improved corrosion resistance and magnetic properties is characterized by having, by weight, C: 0.0005% or more and 0.035% or less, N: 0.005% or more and 0.05% or less, Si: 0.1% or more and 2.0% or less, Mn: 0.1% or more and 0.5% or less, Cr: 16.0% or more and 20.0% or less, Mo: more than 0% and 0.5% or less, Nb: more than 0% and 0.5% or less, Ti: 0.005% or more and 0.30% or less, with the remainder being Fe and unavoidable impurities, and having a value of the following formula (1) of 20 or more. Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn In the formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element.
[0007] The ferritic stainless steel of the present invention preferably has a maximum magnetic permeability value of 1,000 or more in a frequency band of 50 Hz. The ferritic stainless steel of the present invention may have a pitting potential of 200 mV or more. The ferritic stainless steel of the present invention preferably has a surface crystal grain size of 30 μm or more.
[0008] The method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties according to the present invention includes the steps of producing a slab having, by weight percent, C: 0.0005% or more and 0.035% or less, N: 0.005% or more and 0.05% or less, Si: 0.1% or more and 2.0% or less, Mn: 0.1% or more and 0.5% or less, Cr: 16.0% or more and 20.0% or less, Mo: more than 0% and 0.5% or less, Nb: more than 0% and 0.5% or less, Ti: 0.005% or more and 0.30% or less, with the remainder being Fe and unavoidable impurities, and having a value of the following formula (1) of 20 or more; reheating the slab at 1100 to 1300°C; hot rolling the reheated slab and hot annealing it to produce a hot rolled steel sheet; and cold rolling the hot rolled steel sheet, cold annealing it, and pickling it to produce a cold rolled steel sheet. Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn In the formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element.
[0009] In the method for producing a ferritic stainless steel of the present invention, it is preferable that the value of the following formula (2) is 50 or more. Equation (2): [Hot rolling annealing temperature (℃) * hot rolling annealing time (min) + 1.1 * (cold rolling annealing temperature (℃) * cold rolling annealing time (min))] / cold rolling reduction rate (%). In the method for producing a ferritic stainless steel of the present invention, the hot rolling annealing can be carried out at 950 to 1150° C. for 1.5 to 2.5 minutes.
[0010] In the method for producing a ferritic stainless steel of the present invention, the cold rolling annealing is preferably carried out at 1000 to 1200° C. for 1 to 2 minutes. In the method for producing a ferritic stainless steel of the present invention, the cold rolling annealing is preferably carried out at a rolling reduction of 60 to 75%. Effect of the Invention
[0011] According to one embodiment of the present invention, it is possible to provide a ferritic stainless steel having improved corrosion resistance and magnetic properties by optimizing the alloy components and manufacturing process, and a manufacturing method thereof. [Brief description of the drawings]
[0012] [Figure 1] 1 is a graph showing the change in pitting potential according to formula (1). [Diagram 2] 1 is a graph showing a change in maximum magnetic permeability according to formula (2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The ferritic stainless steel with improved corrosion resistance and magnetic properties according to one embodiment of the present invention is characterized by having, by weight, C: 0.0005% or more and 0.035% or less, N: 0.005% or more and 0.05% or less, Si: 0.1% or more and 2.0% or less, Mn: 0.1% or more and 0.5% or less, Cr: 16.0% or more and 20.0% or less, Mo: more than 0% and 0.5% or less, Nb: more than 0% and 0.5% or less, Ti: 0.005% or more and 0.30% or less, with the remainder being Fe and unavoidable impurities, and having a value of 20 or more for the following formula (1): Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn In the formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element.
[0014] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. The following embodiments are presented to fully convey the concept of the present invention to those skilled in the art to which the present invention pertains. The present invention is not limited to the embodiments presented herein and may be embodied in other forms. In the drawings, in order to clarify the present invention, illustrations of parts that are not related to the description may be omitted, and the sizes of components may be somewhat exaggerated to facilitate understanding.
[0015] Throughout the specification, when any part is said to "comprise" a certain element, this does not mean to exclude other elements, but that it may further include other elements, unless specifically stated to the contrary. Any expression in the singular includes any expression in the plural, unless the context clearly indicates otherwise. The reasons for limiting the numerical values of the alloy component contents in the embodiments of the present invention will be described below. In the following, the unit is weight percent unless otherwise specified.
[0016] The ferritic stainless steel with improved corrosion resistance and magnetic properties according to one embodiment of the present invention consists, by weight, of C: 0.0005% or more and 0.035% or less, N: 0.005% or more and 0.05% or less, Si: 0.1% or more and 2.0% or less, Mn: 0.1% or more and 0.5% or less, Cr: 16.0% or more and 20.0% or less, Mo: more than 0% and 0.5% or less, Nb: more than 0% and 0.5% or less, Ti: 0.005% or more and 0.30% or less, with the remainder being Fe and unavoidable impurities.
[0017] The C (carbon) content is 0.0005% or more and 0.035% or less. As the C content increases, the amount of impurities increases, so the C content must be reduced. However, if the C content is too low, refining costs become high. Taking this into consideration, C can be added to 0.0005% or more. However, if the C content is excessive, the elongation rate decreases, the Ductile-Brittle Transition Temperature (DBTT) increases, and impact properties deteriorate. Taking this into consideration, the upper limit of the C content should be 0.035%.
[0018] The N (nitrogen) content is 0.005% or more and 0.05% or less. If the N content is too low, TiN crystallization is reduced, and the equiaxed crystal ratio of the slab is reduced. Taking this into consideration, it is preferable to add N at 0.005% or more. However, if the N content is excessive, the elongation rate decreases and the impact properties deteriorate. Taking this into consideration, the upper limit of the N content is preferably 0.05%.
[0019] The Si (silicon) content is 0.1% or more and 2.0% or less. Silicon is a ferrite phase forming element and can increase hardness. Taking this into consideration, it is preferable to add 0.1% or more of silicon. However, if the silicon content is excessive, the elongation rate decreases, silicon-based inclusions increase, and workability may decrease. Taking this into consideration, it is preferable to limit the silicon content to an upper limit of 2.0%.
[0020] The Mn (manganese) content is 0.1% or more and 0.5% or less. If the Mn content is too low, fine MnS precipitates are formed, which leads to grain refinement and weakened magnetic properties. Taking this into consideration, it is preferable to add Mn in an amount of 0.1% or more. However, if the Mn content is excessive, the proportion of precipitates increases, which may actually result in a decrease in magnetic properties. Taking this into consideration, it is preferable to limit the upper limit of the Mn content to 0.5%.
[0021] The Cr (chromium) content is equal to or greater than 16.0% and equal to or less than 20.0%. Cr, together with Si, is a ferrite phase stabilizing element, and not only plays a major role in securing the ferrite phase, but is also an essential element added to improve corrosion resistance. In consideration of this, it is preferable to add 16.0% or more of Cr. However, if the Cr content is excessive, it promotes the formation of delta (δ) ferrite in the slab, which may reduce the elongation and impact toughness and cause hot rolling sticking defects. In consideration of this, it is preferable to limit the upper limit of the Cr content to 20.0%.
[0022] The Mo (molybdenum) content is more than 0% and not more than 0.5%. Mo, together with Cr, is an element that stabilizes ferrite and is effective in improving corrosion resistance. However, Mo may induce weakening of magnetic properties due to refinement of crystal grains. In consideration of this, it is preferable to limit the upper limit of Mo content to 0.5%.
[0023] The Nb (niobium) content is more than 0% and not more than 0.5%. If the Nb content is excessive, the Nb-based precipitates increase excessively, and the grain size may not be large enough. Therefore, if the Nb content is excessive, there is a risk of a problem of a decrease in magnetic permeability. In consideration of this, it is preferable to limit the upper limit of the Nb content to 0.5% or less.
[0024] The Ti (titanium) content is 0.005% or more and 0.30% or less. Ti is an effective element for improving strength by causing precipitation. In consideration of this, Ti may be 0.005% or more. However, if the Ti content is excessive, it may induce a decrease in magnetic permeability due to the refinement of crystal grains. In consideration of this, it is preferable to limit the upper limit of Ti content to 0.30%.
[0025] The remaining component of the present invention is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and it is impossible to exclude them. Since any engineer of a normal manufacturing process would know about these impurities, the contents of all of them will not be mentioned in this specification.
[0026] In the ferritic stainless steel having improved corrosion resistance and magnetic properties according to one embodiment of the present invention, the value of the following formula (1) is 20 or more. Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn In the formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element.
[0027] FIG. 1 is a graph showing the change in pitting potential according to formula (1). 1, it can be seen that the larger the value of formula (1), the higher the pitting potential. In particular, in order to maintain the pitting potential value at 200 mV or more to ensure high corrosion resistance, it is preferable to control the range of alloy components so that the value of formula (1) is 20 or more.
[0028] The ferritic stainless steel with improved corrosion resistance and magnetic properties according to one embodiment of the present invention has a maximum magnetic permeability value of 1,000 or more in the 50 Hz frequency band. As described later, by controlling the main process factors that affect the magnetic properties of stainless steel, namely the hot rolling annealing temperature, hot rolling annealing time, cold rolling reduction, cold rolling annealing temperature and cold rolling annealing time, it is possible to ensure a maximum magnetic permeability value of 1,000 or more.
[0029] The ferritic stainless steel with improved corrosion resistance and magnetic properties according to one embodiment of the present invention has a surface crystal grain size of 30 μm or more. The finer the surface crystal grain size, the more likely it is that the magnetic properties will be poor. Therefore, the present invention improves the magnetic properties by optimizing the contents of Mn, Mo, Nb, Ti, etc. to control the surface crystal grain size to 30 μm or more.
[0030] Next, a method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties according to the present invention will be described. According to one embodiment of the present invention, a method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties comprises the following components, in weight percent: C: 0.0005% to 0.035%, N: 0.005% to 0.05%, Si: 0.1% to 2.0%, Mn: 0.1% to 0.5%, Cr: 16.0% to 20.0%, Mo: more than 0% and less than 0.5%, Nb: more than 0% and less than 0.5%, Ti: more than 0.5% and less than 0.5%, The method preferably includes the steps of: producing a slab having a content of 0.005% or more and 0.30% or less, with the remainder being Fe and unavoidable impurities, and having a value of 20 or more in the following formula (1); reheating the slab at 1100 to 1300°C; hot rolling the reheated slab and hot-rolling annealing it to produce a hot-rolled steel sheet; and cold rolling the hot-rolled steel sheet, cold-rolling it, annealing it, and then pickling it to produce a cold-rolled steel sheet. Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn In the formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element.
[0031] The component ranges of each alloy composition and the reasons for the numerical limitations of formula (1) are as described above. Each production step will be described in more detail below. First, a slab satisfying the above alloy composition and formula (1) is produced, and then the slab can undergo a series of steps including reheating, hot rolling, hot rolling annealing, cold rolling annealing, and pickling. Next, the produced slab is preferably reheated at 1100 to 1300°C. If the reheating temperature is low, it may be difficult to dissolve the coarse precipitates generated during slab casting. In consideration of this, the reheating temperature should be 1100°C or higher. However, if the reheating temperature is too high, the internal crystal grains may become too coarse. In consideration of this, the upper limit of the reheating temperature is limited to 1300°C.
[0032] In the method for producing ferritic stainless steel with improved corrosion resistance and magnetic properties according to one embodiment of the present invention, the value of the following formula (2) is preferably 50 or greater. Formula (2): [Hot rolling annealing temperature (℃) * Hot rolling annealing time (min) + 1.1 * (Cold rolling annealing temperature (℃) * Cold rolling annealing time (min))] / Cold rolling reduction rate (%)
[0033] FIG. 2 is a graph showing the change in maximum magnetic permeability according to formula (2). 2, it can be seen that the greater the value of formula (2), the greater the maximum magnetic permeability. Therefore, by controlling the value of formula (2), which includes the main process factors that affect the magnetic properties, such as hot rolling annealing temperature, hot rolling annealing time, cold rolling reduction, cold rolling annealing temperature, and cold rolling annealing time, to 50 or more, the magnetic properties of stainless steel can be improved.
[0034] On the other hand, the hot rolling annealing can be carried out at 950 to 1150° C. for 1.5 to 2.5 minutes. If the hot rolling annealing temperature is low or the execution time is short, the crystal grains may not become large enough, which may adversely affect the magnetic properties. However, if the hot rolling annealing temperature is too high or the execution time is too long, the strength may decrease due to the coarsening of the crystal grains. In consideration of this, the hot rolling annealing is preferably performed at 950 to 1150°C for 1.5 to 2.5 minutes, and more preferably at 1000 to 1100°C for 2 to 2.5 minutes.
[0035] The cold rolling annealing can be carried out at 1000 to 1200° C. for 1 to 2 minutes. If the cold rolling annealing temperature is low or the execution time is short, the crystal grains may not be large enough, which may adversely affect the magnetic properties and may reduce the elongation. However, if the cold rolling annealing temperature is too high or the execution time is too long, the strength may decrease due to the coarsening of the crystal grains. In consideration of this, the cold rolling annealing is preferably performed at 1000 to 1200°C for 1 to 2 minutes, more preferably at 1100 to 1200°C for 1.5 to 2 minutes.
[0036] On the other hand, the cold rolling annealing can be carried out at a rolling reduction of 60 to 75%. If the rolling reduction is decreased, the crystal grain size becomes large, which is advantageous from the viewpoint of magnetic properties, but if the rolling reduction is too small, it may be disadvantageous from the viewpoint of workability. Therefore, the cold rolling annealing is preferably performed at a rolling reduction of 60 to 75%.
[0037] The present invention will be described in more detail below through examples. However, it should be noted that the following examples are intended to illustrate and embody the present invention, and are not intended to limit the scope of the present invention. This is because the scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom. {Example}
[0038] Slabs having various alloy composition ranges shown in Table 1 below were produced in a melting furnace. The produced slabs were reheated at 1250°C, and then cold rolled steel sheets were produced by applying the conditions of hot rolling annealing temperature, hot rolling annealing time, cold rolling annealing temperature, cold rolling annealing time and cold rolling reduction shown in Table 2 below.
[0039] [Table 1]
[0040] [Table 2]
[0041] Table 3 below shows the values of formula (1), formula (2), pitting potential, and maximum magnetic permeability. The value of formula (1) was calculated using the following formula (1). Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn In the formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element. The value of formula (2) was calculated using the following formula (2). Formula (2): [Hot rolling annealing temperature (℃) * Hot rolling annealing time (min) + 1.1 * (Cold rolling annealing temperature (℃) * Cold rolling annealing time (min))] / Cold rolling reduction rate (%)
[0042] The pitting potential was measured using a potentiostat. The stainless steel was immersed in a NaCl solution, and a voltage of 20 mV / min was applied. The pitting potential was measured at which the current reached 100 μA. The temperature of the NaCl solution was 30° C., and the concentration was 3.5%. The higher the pitting potential, the better the corrosion resistance. The maximum magnetic permeability was measured using a Single Sheet Test made by Brockhaus Co. Inc. It can be evaluated that the higher the maximum magnetic permeability, the more excellent the magnetic properties.
[0043] [Table 3]
[0044] Referring to Table 3, Examples 1 and 2 satisfied the component range of the alloy composition, formula (1), manufacturing process, and formula (2) specified in the present invention, and had a pitting potential of 200 mV or more and a maximum magnetic permeability of 1000 or more. However, Comparative Examples 1 to 4 did not satisfy the value of formula (1) of 20 or more. Therefore, Comparative Examples 1 to 4 did not satisfy the pitting potential of 200 mV or more. That is, Comparative Examples 1 to 4 had poor corrosion resistance. Moreover, in Comparative Examples 1 to 3 and Comparative Examples 5 to 7, the value of formula (2) did not satisfy 50 or more. Therefore, in Comparative Examples 1 to 3 and Comparative Examples 5 to 7, the maximum magnetic permeability did not satisfy 1000 or more. That is, Comparative Examples 1 to 3 and Comparative Examples 5 to 7 had poor magnetic properties. [Industrial Applicability]
[0045] According to one embodiment of the present invention, it is possible to provide a ferritic stainless steel and a manufacturing method thereof in which the alloy components and manufacturing process are optimized to simultaneously improve the corrosion resistance and magnetic properties, and therefore the industrial applicability is recognized.
Claims
1. In weight percent, C: 0.0005% or more and 0.035% or less, N: 0.005% or more and 0.05% or less, Si: 0.1% or more and 2.0% or less, Mn: 0.1% or more and 0.5% or less, Cr: 16.0% or more and 20.0% or less, Mo: more than 0% and 0.5% or less, Nb: more than 0% and 0.5% or less, Ti: 0.005% or more and 0.30% or less, and the remainder being Fe and unavoidable impurities, A ferritic stainless steel having improved corrosion resistance and magnetic properties, characterized in that the value of the following formula (1) is 20 or more: Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn (In the above formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element).
2. 2. The ferritic stainless steel having improved corrosion resistance and magnetic properties as claimed in claim 1, characterized in that the maximum magnetic permeability is 1,000 or more in a 50 Hz frequency band.
3. 2. The ferritic stainless steel having improved corrosion resistance and magnetic properties according to claim 1, characterized in that the pitting potential is 200 mV or more.
4. 2. The ferritic stainless steel having improved corrosion resistance and magnetic properties according to claim 1, characterized in that the surface crystal grain size is 30 μm or more.
5. In weight percent, C: 0.0005% or more and 0.035% or less, N: 0.005% or more and 0.05% or less, Si: 0.1% or more and 2.0% or less, Mn: 0.1% or more and 0.5% or less, Cr: 16.0% or more and 20.0% or less, Mo: more than 0% and 0.5% or less, Nb: more than 0% and 0.5% or less, Ti: 0.005% or more and 0.30% or less, and the balance being Fe and unavoidable impurities, A step of producing a slab having a value of the following formula (1) of 20 or more; reheating the slab at 1100-1300°C; hot rolling and hot annealing the reheated slab to produce a hot rolled steel sheet; and The method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties includes a step of cold rolling the hot-rolled steel sheet, cold rolling annealing the hot-rolled steel sheet, and pickling the cold-rolled steel sheet. Formula (1): Cr+(3*Mo+10*N+Si+Nb+Ti) / Mn (In the above formula (1), Cr, Mo, N, Si, Nb, Ti, and Mn represent the weight percentage of each element).
6. The method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties according to claim 5, characterized in that the value of the following formula (2) is 50 or more: Equation (2): [hot rolling annealing temperature (°C) * hot rolling annealing time (min) + 1.1 * (cold rolling annealing temperature (°C) * cold rolling annealing time (min))] / cold rolling reduction (%).
7. 6. The method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties according to claim 5, wherein the hot rolling annealing is performed at 950 to 1150° C. for 1.5 to 2.5 minutes.
8. The method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties according to claim 5, wherein the cold rolling annealing is performed at 1000 to 1200° C. for 1 to 2 minutes.
9. 6. The method for producing a ferritic stainless steel having improved corrosion resistance and magnetic properties according to claim 5, wherein the cold rolling and annealing is performed at a rolling reduction of 60 to 75%.
Citation Information
Patent Citations
Ferritic stainless steel having excellent corrosion resistance in condensed water environment generated from hydrocarbon combustion exhaust gas
JP2011184731A
Ferritic stainless steel and method of producing the same
JP2021095610A
Ferritic stainless steel excellent in corrosion resistance in environment of condensed water from hydrocarbon combustion gas
US20130011294A1
Ferritic stainless steel with excellent surface corrosion resistance after polishing, and process for producing same
WO2014157578A1
Ferritic stainless steel with improved corrosion resistance
KR102302386B1
